Kinetic Insights into Cadmium and Lead Removal Using Cellulose-Based Schiff Base Complexes as Adsorbents - Ibrahim, Farah Muaiad (Universitas Gadjah Mada, 2025)
The removal of heavy metals from water is a key environmental challenge. This study focuses on synthesizing and using Schiff base-modified cellulose as adsorbents for cadmium (Cd) and lead (Pb) ions. The materials were developed by modifying cellulose and incorporating Schiff base ligands with Fe(III) and Zn(II) binding sites (Schiffs 1 and 2). Characterization through EDX, SEM, FTIR, elemental analysis, XRD, and TGA confirmed improved surface properties and active adsorption sites. Adsorption followed pseudo-second-order kinetics, indicating chemisorption. The monolayer adsorption capacities for Schiff 1 were 83 mg/g Cd and 78 mg/g Pb, while for Schiff 2, they were 70 mg/g Cd and 63 mg/g Pb. Optimal conditions included solution pH 4.0–5.0, stirring for 45–60 min, 100 mg/L metal concentration, and room temperature (25 ± 2 °C). EDTA efficiently desorbed Cd and Pb for 4 cycles with over 85% efficiency. This study highlights the material’s potential as a cost-effective and eco-friendly solution for wastewater treatment.